Holocene development of maritime ombrotrophic peatlands of the St. Lawrence North Shore in eastern Canada. Issue 1 (July 2014) - Magnan, Gabriel; Garneau, Michelle; Payette, Serge
Abstract: Macrofossil analyses were used to reconstruct long-term vegetation successions within ombrotrophic peatlands (bogs) from the northern shorelines of the St. Lawrence Estuary (Baie-Comeau) and the Gulf of St. Lawrence (Havre-St-Pierre). Over the Holocene, the timing and the ecological context of peatland inception were similar in both regions and were mainly influenced by fluctuations in relative sea level. Peat accumulation started over deltaic sands after the withdrawal of the Goldthwait Sea from 7500 cal yr BP and above silt–clay deposits left by the Laurentian marine transgression after 4200 cal yr BP. In each region, the early vegetation communities were similar within these two edaphic contexts where poor fens with Cyperaceae and eastern larch ( Larix laricina ) established after land emergence. The rapid transitions to ombrotrophy in the peatlands of Baie-Comeau are associated with particularly high rates of peat accumulation during the early developmental stage. The results suggest that climate was more propitious to Sphagnum growth after land emergence in the Baie-Comeau area. Macrofossil data show that treeless Sphagnum -dominated bogs have persisted over millennia and that fires had few impacts on the vegetation dynamics. This study provides insight into peatland vegetation responses to climate in a poorly documented region of northeastern America.